The Effect of Pranayama Meditation and Yogic Practice on High Blood Pressure and Diabetes: The beneficial effects of Yoga exercises on diabetes management and blood pressure control (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The aim of the present study was to investigate theeffect of Yoga exercises- Asanas and Pranayama on diabetic person. Yoga Asanasand Pranayama were conducted on respondents before starting the Asanas andPranayama blood pressure, blood sugar, and hemoglobin were measured. After itwas observed that Asanas and Pranayama have reduced adults ‘blood sugar level,blood pressure and hemoglobin. These changes were observed due to Yogaexercises and it was found at normal level. These observations suggested thatYoga Asanas and Pranayama have a beneficial effect on controlling diabetic symptoms.   It was assumed that there would besignificant effect of Yoga- Asanas and pranayama on blood pressure, bloodglucose and hemoglobin. The results of the study reveal that there issignificant reduction in post-test condition. Yogic exercises showed a positiveand significant impact on diabetic adults.